Fibrinogen-Induced Streptococcus mutans Biofilm Formation and Adherence to Endothelial Cells - Lombardo Bedran, Telma Blanca [UNESP]; Azelmat, Jabrane; Spolidorio, Denise Palomari [UNESP]; Grenier, Daniel (Hindawi Publishing Corporation, 2013)
Streptococcus mutans, the predominant bacterial species associated with dental caries, can enter the bloodstream and cause infective endocarditis. The aim of this study was to investigate S. mutans biofilm formation and adherence to endothelial cells induced by human fibrinogen. The putative mechanism by which biofilm formation is induced as well as the impact of fibrinogen on S. mutans resistance to penicillin was also evaluated. Bovine plasma dose dependently induced biofilm formation by S. mutans. Of the various plasma proteins tested, only fibrinogen promoted the formation of biofilm in a dose-dependent manner. Scanning electron microscopy observations revealed the presence of complex aggregates of bacterial cells firmly attached to the polystyrene support. S. mutans in biofilms induced by the presence of fibrinogen was markedly resistant to the bactericidal effect of penicillin. Fibrinogen also significantly increased the adherence of S. mutans to endothelial cells. Neither S. mutans cells nor culture supernatants converted fibrinogen into fibrin. However, fibrinogen is specifically bound to the cell surface of S. mutans and may act as a bridging molecule to mediate biofilm formation. In conclusion, our study identified a new mechanism promoting S. mutans biofilm formation and adherence to endothelial cells which may contribute to infective endocarditis.